2021
DOI: 10.3390/life11111156
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Physiological Stress Response of Triticum aestivum L. to Glyphosate by Brassinosteroid Application

Abstract: The potential of brassinosteroids to modulate the physiological responses of winter wheat (Triticum aestivum L.) to herbicide stress was evaluated. Young winter wheat seedlings were treated with 24-epibrassinolide (EBL) and 24 h later were sprayed with glyphosate. The physiological responses of treated plants were assessed 14 days after herbicide application. Wheat growth was noticeably inhibited by glyphosate. The herbicide application significantly increased the content of the stress markers proline and malo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 62 publications
2
14
0
Order By: Relevance
“…Moreover, a concomitant decrease in H 2 O 2 burst was also detected in treated plants. This observation is corroborated by other studies, which state that EBL is crucial in altering the performance of antioxidant enzymes, giving cells a better chance of surviving damage brought by stressful conditions [23][24][25][26]. In this study, it was shown that the expression of genes encoding ZmBZR1 and ZmBES1 transcription factors in water-stressed EBL-treated plants was increased, and there was also a concomitant decrease in H 2 O 2 level in plants, indicating that these genes may have a function in ROS detoxification.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Moreover, a concomitant decrease in H 2 O 2 burst was also detected in treated plants. This observation is corroborated by other studies, which state that EBL is crucial in altering the performance of antioxidant enzymes, giving cells a better chance of surviving damage brought by stressful conditions [23][24][25][26]. In this study, it was shown that the expression of genes encoding ZmBZR1 and ZmBES1 transcription factors in water-stressed EBL-treated plants was increased, and there was also a concomitant decrease in H 2 O 2 level in plants, indicating that these genes may have a function in ROS detoxification.…”
Section: Discussionsupporting
confidence: 84%
“…Plants with defects in BR biosynthesis or signaling, in particular, have a dwarf phenotype, indicating that BR is important for normal plant growth and development [21]. Different studies have shown that the exogenous application of BRs increases the tolerance to abiotic stresses by stimulating the enzymatic and non-enzymatic antioxidant defense system [22][23][24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, salinity causes oxidative stress and increases the generation of ROS, which are highly cytotoxic and can react with essential biomolecules including lipids, proteins, and nucleic acids, resulting in lipid peroxidation, protein denaturation, and DNA mutation, respectively [ 3 , 6 ]. Enhancing the activity of plant antioxidant enzymes (superoxide dismutase, catalase, peroxidase, and enzymes involved in the ascorbate–glutathione cycle) is very important to counter oxidative stress [ 13 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…The enzymatic system includes superoxide dismutase (SOD), catalase (CAT), guaiacol peroxidase (POD), ascorbate peroxidase (APX), glutathione peroxidase (GPX), glutathione reductase (GR), glutathione S-transferase (GST), monodehydroascorbate reductase (MDHAR), and dehydroascorbate reductase (DHAR), while the non-enzymatic antioxidants include glutathione (GSH), ascorbic acid (AsA), phenolic compounds, flavonoids, carotenoids, α-tocopherol, etc. (Singh et al 2019;Shen et al 2021;Shopova et al 2021). Salt stress also stimulates methylglyoxal (MG) production.…”
Section: Introductionmentioning
confidence: 99%